The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/00224545.2018.1505709
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of ethnic group membership on bullying at school: when do observers dehumanize bullies?

Abstract: The purpose of this experiment was to test how ethnic group membership of both the bullies and the victims influence the way that observers attribute human characteristics to bullies. Ethnic group membership was manipulated in terms of bullies' and victims' ethnicity (ingroup-majority group versus outgroup-minority group). Furthermore, we examined the mediating role of empathic concern towards the victim and perspective taking of the bully in the relation between ethnic group membership of bullies and victims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The poor internal consistency of the measure in comparison to past research with other groups as the outgroup (e.g. Fousiani et al, 2018) could relate to participants in this study showing greater variation across each trait item rating particularly for autistic people. Kteily et al (2015) compared both subtle measures (such as that used in this study) and blatant measures (e.g.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The poor internal consistency of the measure in comparison to past research with other groups as the outgroup (e.g. Fousiani et al, 2018) could relate to participants in this study showing greater variation across each trait item rating particularly for autistic people. Kteily et al (2015) compared both subtle measures (such as that used in this study) and blatant measures (e.g.…”
Section: Discussioncontrasting
confidence: 81%
“…Likewise, internal consistency was marginally acceptable for human uniqueness traits for ratings of non-autistic people ( ω = 0.63) and poorer for ratings of autistic people ( ω = 0.58). Previous studies have reported good internal consistency for human uniqueness ( ω = 0.85) and human nature traits ( ω = 0.74; Fousiani et al, 2018) although the measure may have low test–retest reliability (Kteily et al, 2015).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In their systematic review of 40 empathy studies, van Noorden et al ( 2014) cited a range of small-to-moderate effect sizes between dispositional PT and bullying experiences that were age group-specific (e.g., for young adolescents aged 11 to 13). Sex consistently determined both empathy dimensions and experiences in bullying processes separately at low levels (van Noorden et al, 2014) as well as ethnical background (Fousiani et al, 2019;Strohmeier et al, 2008).…”
Section: Theoretical Basics Of Belief In a Just Worldmentioning
confidence: 99%
“…Previous research uncovered, as mentioned in Sect. 5, predictive effects of age (van Noorden et al, 2014), gender, ethnical background (Fousiani et al, 2019), and electronic device (Bjereld et al, 2017) that the adolescents used to participate in the online survey were included. We therefore included these variables in our single SEM.…”
Section: Trait Measuresmentioning
confidence: 99%